2004
DOI: 10.1074/jbc.m314027200
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Mimicking and Engineering the Self-organized Structure of Hard Tissues

Abstract: The mechanism of the formation of a self-aligned hydroxyapatite (HAP) nanocrystallite structure was examined. It is found that the highly ordered HAP nanocrystallite assembly is attributed to the so-called self-(homo)epitaxial nucleation and growth. On the other hand, according to this mechanism, a high supersaturation will give rise to a random assembly of HAP crystallites. The effects of ions, biosubstrate, and supersaturation on the micro/nanostructure correlation between substrate and biominerals as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 30 publications
1
81
0
Order By: Relevance
“…On the other hand, it is possible that MTA-F promoted an environment highly saturated with foreign ions, a lower number of cells, and a Ca-Si hydrogel nucleation site. It was shown that relatively high super-saturation gives rise to a compact and random assembly of HAP crystallites (23). In addition, calcium silicate hydrate is the main byproduct of the reaction of MTA with calcium silicate cements (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is possible that MTA-F promoted an environment highly saturated with foreign ions, a lower number of cells, and a Ca-Si hydrogel nucleation site. It was shown that relatively high super-saturation gives rise to a compact and random assembly of HAP crystallites (23). In addition, calcium silicate hydrate is the main byproduct of the reaction of MTA with calcium silicate cements (24).…”
Section: Discussionmentioning
confidence: 99%
“…The diverse conditions of hydroxyapatite nucleation can explain this difference in nanocrystallites morphology. Nucleation is the first step in biomineralization and requires that a free energy barrier be overcome, which results in size and pattern formation of mineral crystallites through the mediating role of many organic and inorganic substrates (23). Super-saturation, foreign ions, cell membrane, and biomolecules, such as bone matrix proteins, may act as regulating agents in controlling the pattern of HAP crystallite assembly.…”
Section: Discussionmentioning
confidence: 99%
“…m is a function of the interfacial free energy difference between the phases of crystal, fluid, and substrate, and it depends on the interaction and interfacial structural match between the crystalline phase and the substrate (27).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, while the mineral constituents is being restored, the region of the exposed collagen fibrils is less susceptible to hydrolytic degradation by MMPs. Furthermore, traditional remineralization by epitaxial growth is a thermodynamically favorable process that overcomes the energy barrier of homogeneous nucleation 41) . According to Ostwald's rule 42) , normally the first occurring phase in polymorphism is the least stable and closest in free energy to the mother-phase, followed by other phases in order of increasing stability.…”
Section: Top-down Remineralization Of Hybrid Layer Collagen Matrixmentioning
confidence: 99%